P138 Moderate-intensity Activity is Associated with Reduced Cardiovascular Risk Factors in COPD. (14th November 2013) - Albarrati, AM; Gale, NS; Enright, S; Munnery, IC; Munnery, MM; Cockcroft, JR; Shale, DJ
Abstract : Background: Steps measurement is a common measure of daily physical activity, but cannot define the intensity of physical activity. Moderate intensity activity is recommended type to maintain a basic level of health (1), but in patients with COPD, the effect of moderate intensity activity on systemic manifestations has not been studied. We hypothesised that patients with higher moderate activity time would have lower frailty, inflammation and cardiovascular risk. Methods: As part of a longitudinal study in COPD (ARCADE), daily physical activity was recorded over seven days using a multisensor armband (SenseWear Pro armband) in 75 stable patients with COPD. Spirometry, body composition, aortic stiffness, comprehensive geriatric assessment, C-reactive protein (CRP) and fibrinogen were also determined. Moderate-intensity activity was determined by the monitor for activity between 3 to 6 METs. Results: Patients (42 males) mean (SD) age was 66 (7) years, BMI 27.5 (5.2) Kg/m 2, FEV1 predicted 55 (17)% and moderate activity time 1.46 (1.23) hours. The time spent on moderate activities was not related to age or FEV1 pred. The moderate activity time related to BMI (r = -0.41), fat mass (r = -0.38) and fat percentage (r = -0.37), all p < 0.001, but not with fat free mass. However, none of these parameters related to the number of steps. Moderate activity time was inversely associated with aortic stiffness, r = -0.31, p < 0.01, CRP, fibrinogen (r = -0.26; r = -0.24, respectively) and frailty score all p < 0.05. However, the number of steps only related to the inflammatory markers. Conclusion: The changes in frailty and cardiovascular risk factors including adipose tissue, aortic stiffness and inflammatory markers are linked to the proportion of time in moderate activities as their predominant form of activity. References: Elsawy, B and Higgins, K. (2010) Am Fam Physician 1;81(1):55–59.